Observation of Giant Infrared Circular Dichroism in Plasmonic 2D-Metamaterial Arrays - Knipper, Richard; Mayerhoefer, Thomas G.; Kopecky, Vladimir; Huebner, Uwe; Popp, Juergen (ACS Photonics, 2018)
We report the observation of an enormous circular dichroism (CD) response in broadband surface-enhanced infrared absorption sensing arrays. In our experiment, a 2D-metamaterial chiral cross-slit array adjusted for application in conventional measurement setups was used. The inherent chirality of the design results in a very strong CD absorbance of 0.83 at around 2.86 μm (3500 cm-1). This far surpasses our predictions based on the finite-difference time-domain simulations. This is probably the highest CD response ever reported for the mid-infrared region. Our observation was rigorously validated; thus most error sources were ruled out. Further, this Letter discusses our results in view of possible remaining artifacts that might have had an influence on our observations, as both chiral enantiomers and an achiral counterpart with similar structure were created and measured. A giant CD 2D-metamaterial might lead toward surface-enhanced vibrational circular dichroism spectroscopy, a field that is subject to lively discussions.
CRIS-Team Scopus Importer:2023-04-20
Keywords: chiral plasmonics; infrared spectroscopy; metamaterials; surface enhancement; vibrational circular dichroism